The influence of positive psychological capital, job stress, and burnout on infection control fatigue in emergency room nurses - Lee, Yun Jeong; Kang, Ji Soon; Hwang, Ji Won (Edelweiss Applied Science and Technology, 2025)
This study aimed to investigate the factors influencing infection control fatigue among emergency room nurses, specifically examining the roles of job stress, burnout, and positive psychological capital. A cross-sectional survey was conducted with 170 emergency nurses using validated instruments. Data were analyzed using descriptive statistics, Pearson’s correlation, and multiple regression analysis. The findings indicated that infection control fatigue was positively correlated with job stress (r = .750, p < .001) and burnout (r = .428, p < .001), while a negative correlation was observed with positive psychological capital (r = –.085, p = .136). Multiple regression analysis revealed that these variables collectively explained 58.9% of the variance in infection control fatigue. The results underscore the critical need to address occupational stressors and emotional exhaustion in emergency settings. Enhancing positive psychological capital may serve as a protective factor, reducing fatigue and improving infection control compliance. Practical implications include the implementation of institutional strategies such as stress management programs, resilience training, and supportive leadership to sustain frontline nurse well-being and performance.